Post-partum family planning in Burkina Faso (Yam Daabo): a two group, multi-intervention, single-blinded, cluster-randomised controlled trial. Issue 8 (August 2019) - Tran, Nguyen Toan; Seuc, Armando; Coulibaly, Abou; Landoulsi, Sihem; Millogo, Tieba; Sissoko, Fatou; Yameogo, Wambi Maurice E; Zan, Souleymane; Cuzin-Kihl, Asa; Kiarie, James; Gaffield, Mary Eluned; Thieba, Blandine; et al.
Summary: Background: Post-partum family planning services can prevent maternal and child morbidity and mortality in low-resource settings. We assessed the effect of a family planning intervention package on modern contraceptive use at 12 months post partum in predominantly rural Burkina Faso. Methods: Yam Daabo was a two group, multi-intervention, single-blinded, cluster randomised controlled trial. Primary health-care centres were randomly allocated to intervention or control clusters in a 1:1 ratio with only data analysts masked to the allocation assignment. Interventions comprised refresher training for the provider, a counselling tool, supportive supervision, availability of contraceptive services 7 days a week, client appointment cards, and invitation letters for partners. The primary outcome was modern contraceptive prevalence at 12 months, and secondary outcomes were modern contraceptive prevalence at 6 weeks and 6 months post partum. Analysis was by modified intention to treat. Prevalence ratios were adjusted for cluster effects and baseline characteristics. This study was registered with the Pan-African Clinical Trials Registry (PACTR201609001784334). Findings: From July 27–Oct 17, 2016, eight clinics were randomised and 571 women were enrolled and allocated: 286 to four intervention clusters and 285 to four control clusters. Of these, 523 completed the 12-month study exit interview (260 in the intervention group, 263 in the control group) and 523 were included in the intention-to-treat analysis. At 12 months, modern contraceptive prevalence was 55% among women who received the package and 29% among those who received routine care in control clusters (adjusted prevalence ratio 1·79, 95% CI 1·30–2·47). Significant differences in modern contraceptive prevalence were also seen between intervention and control groups at 6 weeks (42% and 10%, respectively; adjusted prevalence ratio 3·88, 95% CI 1·46–10·35) and 6 months (59% and 24%, respectively; 2·31, 1·44–3·71). Interpretation: A package of six low-technology interventions, aimed at strengthening existing primary health-care services and enhancing demand for these services, can effectively increase modern contraceptive use for up to a year post partum in rural settings in Burkina Faso and has the potential to be suitable in similar settings in this country and others. Funding: Government of France.